2014
DOI: 10.1177/0284185113493086
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT imaging of skeletal muscle metastases

Abstract: SMM manifested on PET/CT as focal hypermetabolic intramuscular areas with different SUV. There were no significant differences between SUV or size of the identified SMM in esophageal cancer, renal cell carcinoma, and lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Skeletal muscles are usually at the periphery of the FOV of chest or abdomen CT scans, and are apt to receive less attention. Recently SMM from various malignancies have been reported in several case reports and a few clinical studies of PET-CT due to its almost complete covering of the whole body and higher sensitivity (6,(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skeletal muscles are usually at the periphery of the FOV of chest or abdomen CT scans, and are apt to receive less attention. Recently SMM from various malignancies have been reported in several case reports and a few clinical studies of PET-CT due to its almost complete covering of the whole body and higher sensitivity (6,(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of skeletal muscle metastasis (SMM) among cancer patients varies, in the range of 0.03-17.5%, with a relatively higher prevalence of [6][7][8][9][10][11][12][13][14][15][16][17].5% in autopsy studies (2,3) compared to 0.03-5.6% in clinical imaging-based studies (4)(5)(6), indicating that more sensitive imaging modalities are required to detect SMM (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bocchino et al reported that 18-fluoro-fluorodeoxyglucose ( 18 F-FDG) uptake in muscle metastatic lesions increased homogeneously reaching a higher maximum standardized uptake value (SUV max ) (mean value 4.2 ± 2.8) than in the liver [11]. Surov et al reported PET/CT findings of skeletal muscle metastases from different primary tumors [14]. Identified skeletal muscle metastases presented as intramuscular focal abdominal activity with SUVs ranging from 2.4 to 25.9, median SUV 7.8.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous case reports and, more recently, larger group studies have characterized the imaging appearance of such metastases on CT, MRI and PET/CT [913]. On MRI, skeletal muscle metastases typically manifest as well defined intramuscular lesions that are isointense to normal muscle on T1-weighted and hyperintense to normal muscle on T2-weighted sequences, with marked enhancement [11, 13].…”
Section: Introductionmentioning
confidence: 99%